ALTERNATIVE METHODS FOR IMPROVING BALANCE IN STROKE RECOVERY: VISUAL AND VERBAL CUES AS COST-EFFECTIVE MODALITIES - RAO, LAKSHITA SINGH; LOHAR, DEEPAK; KHAN, JAFAR; KALYANA, SHUBHAM (International Journal of Current Pharmaceutical Research, 2023)
Objective: Stroke is a significant global health concern, leading to high mortality and disability rates. Prompt assessment, management, and rehabilitation are crucial for improving clinical outcomes. Balance impairment is a common consequence of stroke, affecting the majority of survivors and increasing the risk of falls and disability. Methods: The study included 30 post-stroke hemiplegic individuals, randomly assigned to a control group and an experimental group. The control group received conventional physical therapy, while the experimental group received additional visual and verbal feedback. The Berg Balance Scale was used to assess balance on days 1, 15, and 30. Results: Both groups showed improvements in balance scores over time. However, the experimental group consistently had higher scores, indicating a greater effect of incorporating visual and verbal cues with conventional therapy. Conclusion: Our study demonstrates that the combination of visual and verbal cues with conventional therapy leads to improved balance outcomes in stroke recovery. These findings support the benefits of visual feedback, verbal feedback, and mirror therapy in stroke rehabilitation. Incorporating these alternative methods can be cost-effective and accessible interventions to enhance balance, reduce fall risk, and improve the overall recovery and quality of life in stroke survivors.